Integration concept of Taoist sites in Jiangxi province: Interpretation, analysis and sustainable tourism - Liu, Xin (Thai Journal of East Asian Studies, 2024)
This paper aims to help Taoist heritage sites achieve sustainable tourism. Mount Longhu has been related to the Zhengyi sect of Taoism since the Song Dynasty, and the neighboring San Qing Gong and Tiezhu Palace temple complexes should be examined as part of the Taoist landscape for sustainable tourism. The cultural significance of the Burra Charter for sustainable heritage management will be used as principal methodology, supplemented by field study. Results show that integrating authentic Taoist sites in Jiangxi Province, China demonstrate the relative completeness of the Taoist landscape and form a solid basis for sustainable local tourism.